The Requirements of Activating the Function of Internal Auditing in Government Institutions - امهدرسث امدكخِرة شنٔر غتدامرضىي رشٔد; المدرسث امىساغدة حِرٓي ًتٔل غتدامرضىي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims to activate the internal audit function in government units in the city of Dohuk, through many of the necessary requirements that must be available in the internal audit function in order to achieve the desired goals, the study examined both the Independence and function site for the unity of the audit, look at the senior management of the function audit, as well as the expertise and efficiency of the staff and audit unit as requirements to activate the internal audit function. For the fulfillment of the study’s goals, nine main hypotheses were built to examine the reality of variants of the study, in the field side was descriptive and analytical approach based reliance on analysis and interpretation of the case and the internal audit function as a function of important functions in government institutions, as has been the use of the questionnaire form for the special requirements of data activation of the internal audit function through the opinions poll internal auditors of the institutions (8) selected in the city of Dohuk, and was unpacking and analysis of the questionnaire through the use of statistical and analytical (SPSS) program where the use of appropriate statistical tests. Based on this, the study has reached a set of conclusions was the most prominent of which, there is a marked weakness in the performance of the internal audit function in the sample under study is due to a combination of reasons, most notably the lack of qualified personnel with expertise in the area of specialization as well as the weakness of independence in the performance of auditors internal to his duties .on him study recommended the need to activate the internal audit function through the use of personnel with competence and experience high as well as the need to train internal auditors training program annually, as stipulated by international auditing standards, either in terms of independence, should provide an atmosphere of far independence from all the pressures of others sound practices by the higher authorities in order to reap the internal audit process of the desired benefits.